Congenital scoliosis associated with agenesis of the uterine cervix. Case report - Monica Matteo; Di Blasi Arturo; Carlomagno Giorgio (BMC, 2004)
Abstract Background Alterations in the normal sequence of development of müllerian ducts lead to a wide spectrum of reproductive tract abnormalities. A rare form of lack of development, regarding a short tract of the müllerian ducts, leads to the isolated agenesis of the uterine cervix. Anomalies identified among patients with müllerian agenesis include skeletal deformities (i.e., scoliosis of the spine and Klippel-Feil anomaly). Case presentation A 46 years old woman presenting cyphoscoliosis and very low stature (120 cm - 3,93 feet), came to our observation for acute pelvic pain; she also reported primary amenorrhoea associated with cyclic pelvic pain. Clinical and imaging evaluation, evidenced a blind vaginal duct of normal length, left cystic adnexal mass, and enlarged uterus with hematometra. FSH, LH, 17β estradiol and CA-125, karyotype and radiographic study of limbs and vertebral column were also evaluated. At laparotomy, a left ovarian cyst was found. Uterus ended at the isthmus; under this level a thin fibrous tissue band was found, joining the uterus to the vagina. Uterine cervix was replaced by fibrous tissue containing some dilated glands lined with müllerian epithelium. Karyotype resulted 46, XX. The described skeletal deformity, were consistent with Klippel-Feil syndrome. Conclusion We report a case of congenital scoliosis associated with müllerian agenesis limited to uterine cervix, association thus far seen only among patients with Mayer-Rokitansky-Kuster-Hauser syndrome (utero-vaginal agenesis). This case report supports the necessity to evaluate, for accompanying müllerian anomalies, all cases of congenital structural scoliosis in view of the possibility for many müllerian development abnormalities, if timely diagnosed, to be surgically corrected.